2019
DOI: 10.3390/microorganisms7030077
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak History, Biofilm Formation, and Preventive Measures for Control of Cronobacter sakazakii in Infant Formula and Infant Care Settings

Abstract: Previously known as Enterobacter sakazakii from 1980 to 2007, Cronobacter sakazakii is an opportunistic bacterium that survives and persists in dry and low-moisture environments, such as powdered infant formula. Although C. sakazakii causes disease in all age groups, infections caused by this pathogen are particularly fatal in infants born premature and those younger than two months. The pathogen has been isolated from various environments such as powdered infant formula manufacturing facilities, healthcare se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 51 publications
1
73
0
2
Order By: Relevance
“…Cronobacter sakazakii, as described by Iversen et al [1] consists of a group of strains previously reported by Farmer et al [59] as belonging to biogroups 1-4, 7, 8, 11, and 13 of the former E. sakazakii species epithet. C. sakazakii is the predominant Cronobacter species associated with infantile and adult illnesses [4][5][6][7][8][13][14][15]18]. Using the multi-locus sequence typing (MLST) scheme described by Baldwin et al [60], Joseph et al [61], and Joseph and Forsythe [62] showed an association among particular C. sakazakii sequence types (ST), which are found with specific types of illnesses [63,64].…”
Section: Cronobacter Sakazakiimentioning
confidence: 99%
See 2 more Smart Citations
“…Cronobacter sakazakii, as described by Iversen et al [1] consists of a group of strains previously reported by Farmer et al [59] as belonging to biogroups 1-4, 7, 8, 11, and 13 of the former E. sakazakii species epithet. C. sakazakii is the predominant Cronobacter species associated with infantile and adult illnesses [4][5][6][7][8][13][14][15]18]. Using the multi-locus sequence typing (MLST) scheme described by Baldwin et al [60], Joseph et al [61], and Joseph and Forsythe [62] showed an association among particular C. sakazakii sequence types (ST), which are found with specific types of illnesses [63,64].…”
Section: Cronobacter Sakazakiimentioning
confidence: 99%
“…Urmenyi and Franklin, in 1961, reported the first cases of fatal invasive newborn infections (meningitis) caused by Cronobacter species (reported as a yellow-pigmented Enterobacter cloacae) [16]. Furthermore, Cronobacter was elevated to a global foodborne and public health issue when contaminated lots of powdered infant formula (PIF) or follow-up formula (FUF) were epidemiologically linked to several neonatal and infant septicemia/meningitis outbreaks [17][18][19]. In addition to meningitis, the range of Cronobacter infantile infections have been extended now to include necrotizing enterocolitis (NEC) and bacteremia or sepsis; death can occur within hours from the onset of symptoms [4][5][6][7][8][9]11,13,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Ethiopia it is assumed that the number of infections caused by Cronobacter sakazakii is under reported. Unlike the vast majority of main foodborne pathogens, Cronobacter sakazakii infections are not currently a reportable disease in nearly all states [7]. Cronobacter sakazakii is a threat to infant, neonatal and other susceptible age groups resulted from utilizing contaminated powder infant formula or utensils such as spoons used for reconstitution ( Figure 1).…”
Section: Infant Food Contamination By Cronobacter Sakazakiimentioning
confidence: 99%
“…In addition, a known contaminant of formula powder is Chronobacter (formerly Enterobactor) sakazakii. This bacteria is found primarily in dry and dehydrated foods with low water activity, such as herbal teas, starches, and in powdered infant formula [93]. In formula-fed infants it can occasionally cause infections and fatal neonatal cases have been reported from Japan [94].…”
Section: Infection From Infant Formulamentioning
confidence: 99%